ON THE STARK BROADENING OF Ar VII SPECTRAL LINES - Dimitrijević, Milan S.; Sahal-Bréchot, Sylvie (Bulletin of Natural Sciences Research, 2017)
Stark broadening parameters, full width at half maximum of spectral line and shift, have been calculated for 3 spectral lines of Ar VII, for broadening by electron, proton, and He III impacts. For calculations, the semiclassical perturbation approach in the impact approximation has been used. The results are provided for temperatures from 20 000 K to 500 000 K and for an electron density of 1017 cm-3. Obtained results will be included in the STARK-B database which is also included in Virtual atomic and molecular data center (VAMDC).